Barriers and Facilitators to Managing Multiple Chronic Conditions: A Systematic Literature Review. (April 2015) - Koch, Gina; Wakefield, Bonnie J.; Wakefield, Douglas S.
The prevalence of multiple chronic conditions (MCC) is increasing, creating challenges for patients, families, and the health care system. A systematic literature search was conducted to locate studies describing patient's perceptions of facilitators and barriers to management of MCC. Thirteen articles met study inclusion criteria. Patients reported nine categories of barriers including financial constraints, logistical challenges, physical limitations, lifestyle changes, emotional impact, inadequate family and social support, and the complexity of managing multiple conditions, medications, and communicating with health care providers. Four facilitators were found, including health system support, individualized care education and knowledge, informal support from family and social systems, and having personal mental and emotional strength. Existing research on management of MCC from the patient's perspective is limited. Interventions are needed to improve management practices with particular attention to the knowledge and skills required by this unique population.